2006
DOI: 10.1080/09553000600857389
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of differentially expressed genes in mouse bone marrow tissues after ionizing radiation

Abstract: Ionizing radiation (IR) affects the expression of a series of genes including genes involved in G1/S transition and the P53 pathway. Among those, reduction of SIRT1 was seen to be involved in transactivation of P53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…Therefore, we can conclude that the responses of irradiated bone marrow tissue are different at the stage of injury compared to recovery. For example, p53 and its downstream target genes (such as, cyclin G1 and Bax ) which induce cell-cycle arrest, DNA repair and apoptosis are up-regulated after IR [8], [32], but we observed no expression change of these genes during the recovery phase in our experiment.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Therefore, we can conclude that the responses of irradiated bone marrow tissue are different at the stage of injury compared to recovery. For example, p53 and its downstream target genes (such as, cyclin G1 and Bax ) which induce cell-cycle arrest, DNA repair and apoptosis are up-regulated after IR [8], [32], but we observed no expression change of these genes during the recovery phase in our experiment.…”
Section: Discussioncontrasting
confidence: 61%
“…Microarray analysis of irradiated mice at the recovery phase has not been report so far. Dai et al reported that in murine BM 6 h after 6.5 Gy gamma irradiation, the functional categories of differentially expressed genes are comprised of biological processes including DNA replication/repair, proliferation/apoptosis, cell cycle control and RNA processing [8]. Therefore, we can conclude that the responses of irradiated bone marrow tissue are different at the stage of injury compared to recovery.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, upon immune activation, Th polarization is shifted towards the Th 1 -type reactions and this evolves into a more effective immune response. Since the first days after irradiation are especially characterized by inflammatory processes [27], this altered immune milieu in HDC -/-mice could explain the more protective reactions observed during the early phase of extramedullary hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%